Emerging perspectives on the mobile content evolution - Aguado, Juan Miguel; Feijóo, Claudio; Martínez, Inmaculada J. (Advances in multimedia and interactive technologies (AMIT) book series, 2016)
This book seeks a better understanding of the centrality of mobile content in the recent and coming evolution of both the ICT ecosystem and the media industry for those within the interdisciplinary field of media studies, covering topic areas such as journalism, marketing and advertising, broadcasting, information management, media management, media economics, media- and technology-related public policies